Traumatic Healing Responsiveness in Frost’s “Birches” - Pokharel, Bishnu Prasad (Literary Studies, 2024)
Robert Frost’s poem “Birches” raises the issue of nature conservation to disengage mankind from the humdrum of the mundane world, advocating a symbiotic world that encompasses trivial and sublime things of the world. Frost's concern for wildlife conservation aims at providing a sanctuary for all people who are struggling against the onslaught of socio-economic challenges, family predicaments, and the inescapable effects of social media. This article argues that the turbulent mind does not work for the supportable advancement of humanity; Frost’s poem is a plea for a return to the pristine glory of nature as a healing agent for the miseries and dismays perpetrated on human beings by modern civilization. The poet appeals to the public apprehension for the benefit of the human race through verse. Using the ecocritical lens, this paper engages the qualitative research methodology to analyze the poem. The interpretation is based on the data pooled from secondary sources by reviewing the literature existing in the paradigm of eco-critical theory. Critical readings are based on the concept that nature is tantamount to spiritual therapy providing emotional alliance with it. This study incorporates critics' versions, text, and reference books as the sources to justify the argument. It contributes to the development of ecological cognizance for nature preservation that in turn provisions for reducing the psychological trauma among the modern people. The findings support the policy designers to take effective steps to reduce the damaging facets and provision to plan for sustainable development.